Dampak Sistem Informasi (SIPESMA) Terhadap Efektivitas Pengelolaan Sampah Di Mamuju - Lilis Andini; Rastina Fitri; Hari Yeni (Jurnal Ilmu Manajemen dan Akuntansi Nusantara, 2026)
The development of information technology offers significant opportunities to improve the effectiveness of waste management at the regional level. The Waste Management Information System (SIPESMA) has emerged as a digital innovation developed by local governments to monitor, coordinate, and optimize waste management services. This study aims to analyze the impact of SIPESMA implementation on the effectiveness of waste management in Mamuju Regency. The research method employs a qualitative descriptive approach through literature analysis, review of regional policies, and phenomenological observation. The results indicate that SIPESMA enhances reporting speed, accuracy of waste generation data, responsiveness of field officers, and community participation. However, technical constraints, limited human resources, and low levels of digital literacy among the community hinder system optimization. The study concludes that SIPESMA has a positive and significant impact on the effectiveness of waste management services, although improvements in capacity building and stronger infrastructure support are required.